Hubungan antara Religiusitas dengan Kecemasan karyawan Parahita Diagnostic Center saat Menghadapi Virus Covid 19 - Muzakki, Moch (Academicia Globe: Inderscience Research, 2020)
The phenomena that occurred at the Parahita Diagnostic Center during the Covid 19 pandemic had an impact on everyone. One of them had an impact on the anxiety of the employees of the Surabaya branch of the Parahita Diagnostic Center. This study aims to determine the relationship between religiosity and anxiety. The number of this study amounted to 120 employees from a total population of 120 employees. The sampling technique used is Non Probabil Sampling. While the data was taken using the anxiety scale adapted from Nugroho's research (2010) and the Religiosity scale adapted from Huber & Huber (2012) with reliable scores of 0.903 and 0.772. The results of this study used Shapiro Wilk's analysis assisted by SPSS for Windows and showed a relationship There is a significant positive relationship between Religiosity and Anxiety with a correlation coefficient of p = - 0.362 with a significance value of P = 0.000. This means that the research hypothesis is accepted. So, it can be concluded that the higher the Religiosity, the lower the Anxiety of Parahita Diagnosti Center employees during the Covid-19 Pandemic. The result shows the effective contribution of religiosity to anxiety of 13.1% while 86.9% is influenced by other factors.